Tafsir Al Qur’an Tentang Pendidikan Memelihara Lingkungan - Hapid, Hapid; Hidayat , Agus (Neolectura, 2025)
The interpretation of the Qur'an related to education in preserving and protecting the environment has significant relevance in addressing current global environmental challenges. This article aims to examine Qur'anic verses that emphasize the importance of a harmonious relationship between humans and the environment and their implications for ecological education. A thematic approach is employed to analyze Qur'anic verses such as QS. Al-Baqarah: 205, QS. Al-A'raf: 31, and QS. Ar-Rum: 41, which highlight humanity's responsibility as stewards (khalifah) on Earth. This study reveals that the Qur'an provides fundamental principles for maintaining ecosystem balance, including the prohibition of corruption (fasad), wise resource management, and respect for Allah's creations. In the context of education, these values can be implemented by integrating Qur'anic teachings into formal and non-formal education curricula to foster ecological awareness from an early age. The findings of this study are expected to contribute both theoretically and practically to developing an education paradigm based on the values of rahmatan lil 'alamin to achieve environmental sustainability.